Practical Application of the Leagile Concept in Production Management through the Alignment of Flexibility and Efficiency. The Case of a Home Appliance Manufacturing Company - Stobiński, Robert (Studia Oeconomica Posnaniensia, 2015)
Currently it is generally assumed that the lean supply chain focused on waste elimination and cost reduction in the face of increasing volatility and complexity in the market should be replaced by agility, focused on the flexibility and responsiveness to change. This article, based on a case study, presents an alternative approach using a combination of both strategies into a Leagile solution. The common objective of which is to meet the needs of customers' and shareholders' expectations and which fully justifies this approach.